The light and shadows of Ukrainophilia: the state policy of ukrainization and indigenization in the USSR in the 1920s - R.R. Akzhigitov (Известия высших учебных заведений. Поволжский регион: Общественные науки)
Background. The article is devoted to the strengthening of Ukrainian nationalism in the first years of the USSR in connection with the state policy of Ukrainization and indigenization, which allows us to understand the origins of the modern version of the concept of Ukrainophile exclusivity. The author sets the task of analyzing the objective picture of the mixing of ethnic groups in Ukraine and the subjective efforts of the Ukrainian ethnocracy to transition to ethnic dominance. The motives of the federal center for sanctioning the implementation of the policy of Ukrainization and indigenization are revealed. Materials and methods. A whole series of publications on the ethnolinguistic situation in Ukraine in the second half of the 19th century – 1920s, statistical and party sources (stenographic reports of the 12th Congress of the RCP(b) and the 4th meeting of the Central Committee of the RCP(b) are used. The author uses methods of analysis and synthesis, comparison, and publishes important tabular material. Results. The absence of Ukraine as a single territorialadministrative massif spurred the Ukrainophile intelligentsia, in the conditions of revolutionary destabilization of 1917, to ideological and territorial expansion in the person of the Kyiv Central Rada. However, during the Civil War, supporters of the petty-bourgeois nationalist idea did not receive priority support – Ukraine nevertheless became Soviet. Nevertheless, the Bolsheviks, fearing Ukrainophilia, made unjustified concessions to the latter. They were expressed in the forced integration of Novorossiya into Ukraine, and later in the policy of linguistic Ukrainization of languages. But very soon the formal equality of languages was transformed into the provision of personnel and material preferences to the bearers of the idea of Ukrainianism. It was defended in the party and bureaucratic elite by H.G. Rakovsky, N.A. Skrypnik, G.F. Grinʼko, A.Ya. Shumsky, V.P. Zatonsky, V.Ya. Chubar. Initially, the course towards Ukrainianization was actually sabotaged at the bottom, but with the arrival of the tough Stalinist appointee L.M. Kaganovich, a turning point occurred. At the same time, the nationalistic outrages in which individual representatives of the creative intelligentsia, such as M. Khvylovy, were noticed, prompted the central government to become wary and the campaign gradually began to wind down. Conclusions. The policy of Ukrainization should be considered as part of the course of indigenization, which provided for worldwide assistance in the socio-cultural development of indigenous ethnic groups. In the context of Ukraine, the passion for this policy, along with its positive culturalcomponent, was fraught with many dangers due to the size and strategic importance of the republic, its ethnic heterogeneity (primarily the presence of Russian-speaking Novorossiya), and the aggressiveness of Ukrainian chauvinism, which dreamed of subjugating Russian-speaking cities. Finally, the situation was complicated by the protracted flirtation with the nationalists on the part of the center, which was largely abandoned only in the early 1930s.